Russell & Co. records - Russell & Co.; Russell, Samuel, 1789-approximately 1862.
Correspondence, financial and legal records, and miscellany relating to Russell & Co., Guangzhou (Canton), China, and to its founder, Samuel Russell, and members of his family. Includes material relating to the merger of Russell & Co. with John P. Cushing, William Perkins & Company of Boston, Mass., and Houqua, of Guangzhou, China; banking problems in the U.S.; national and international monetary matters; commerce with China; commerce within the U.S.; the Russell Manufacturing Company, producer of elastic webbing, established in Middletown, Conn., in 1831; Ithiel Town's design of Samuel Russell's Middletown mansion; land speculation in Illinois, Kentucky, Michigan, New Jersey, Ohio, and Wisconsin; the Turkish opium trade; the American Colonization Society; and epilepsy and the medical care of Russell's son, John A. Russell.
Family correspondence chiefly between Samuel Russell and his sons, George O. Russell and John A. Russell, and his brother, Edward Augustus Russell. Other correspondents include J.W. Alsop, Richard Alsop, Philip Ammidon, John Jacob Astor, Cyrus Butler, John Murray Forbes, R.B. Forbes, Augustine Heard, Gurdon Saltonstall Hubbard, S.D. Hubbard, William Henry Low, W.L. Newberry, Ithiel Town, Samuel Wetmore, and William Wetmore. Firms represented by correspondence include Baring Brothers & Co., Benjamin & Thomas C. Hoppins, Clarke & Company, of Smyrna, Turkey, Edward Carrington & Company, George Douglas & Company, Hull & Griswold, and Ward & Bartholomew.
Microfilm edition available
Microfilm produced from the originals in the Manuscript Division.
Trading house founded in 1819 by Samuel Russell of Middletown, Conn., in Guangzhou (Canton), China.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alsop, J. W. -- 1804-approximately 1878 -- Correspondence; Alsop, Richard, -- 1761-1815 -- Correspondence; Ammidon, Philip -- Correspondence; Astor, John Jacob, -- 1763-1848 -- Correspondence; Butler, Cyrus, -- 1767-1849 -- Correspondence; Forbes, John Murray, -- 1771-1831 -- Correspondence; Forbes, R. B. -- 1804-1889 -- Correspondence; Heard, Augustine, -- 1785-1868 -- Correspondence; Hubbard, Gurdon Saltonstall, -- 1802-1886 -- Correspondence; Hubbard, S. D. -- 1799-1855 -- Correspondence; Low, William Henry, -- 1816-1845 -- Correspondence; Newberry, W. L. -- 1804-1868 -- Correspondence; Russell, Edward Augustus, -- 1797- -- Correspondence; Russell, George O. -- Correspondence; Russell, John A., -- active 1838-1846 -- Correspondence; Town, Ithiel, -- 1784-1844.; Town, Ithiel, -- 1784-1844 -- Correspondence; Wetmore, Samuel, -- approximately 1813-1885 -- Correspondence; Wetmore, William, -- 1776- -- Correspondence; Russell family; American Colonization Society; Baring Brothers & Co. -- Correspondence; Benjamin & Thomas C. Hoppins (Firm) -- Correspondence; Clarke & Company -- Correspondence; Claude Daniel Crommelin & Sons -- Correspondence; Edward Carrington & Company -- Correspondence; George Douglas & Company -- Correspondence; Houqua (Trading company); Hull & Griswold -- Correspondence; John P. Cushing, William Perkins & Company; Russell Manufacturing Company; Ward & Bartholomew -- Correspondence; William Perkins & Company; Architecture -- Connecticut -- Middletown; Banks and banking -- United States; Cotton manufacture -- Connecticut -- Middletown; Epilepsy; Land speculation -- Illinois; Land speculation -- Kentucky; Land speculation -- Michigan; Land speculation -- New Jersey; Land speculation -- Ohio; Land speculation -- Wisconsin; Medicine -- History -- 19th century; Monetary policy; Monetary policy -- United States; Opium trade -- Turkey; China -- Commerce -- United States; Guangzhou (China) -- Commerce; United States -- Commerce -- History -- 19th century; United States -- Commerce -- China